Comparison of two-dimensional methods versus three-dimensional scanning systems in the assessment of total body surface area estimation in burn patients. Issue 1 (February 2018) - Retrouvey, Helene; Chan, Justin; Shahrokhi, Shahriar
Highlights: Accuracy of %TBSA estimation was compared between conventional and 3D methods. BurnCase 3D underestimated %TBSA by 1.3% as compared to conventional methods. This difference minimally impacted fluid resuscitation (not clinically significant). BurnCase 3D program was found to be a valid tool for %TBSA estimation. BurnCase 3D should be considered at centers without experienced burn surgeons. Abstract: Background: Accurate measurement of percent total body surface area (%TBSA) burn is crucial in the management of burn patients for calculating the estimated fluid resuscitation, determining the need to transfer to a specialized burn unit and probability of mortality. %TBSA can be estimated using many methods, all of which are relatively inaccurate. Three-dimensional (3D) systems have been developed to improve %TBSA calculation and consequently optimize clinical decision-making. The objective of this study was to compare the accuracy of percent total burn surface area calculation by conventional methods against novel 3D methods. Methods: This prospective cohort study included all acute burn patients admitted in 2016 who consented to participate. The staff burn surgeon determined the %TBSA using conventional methods. In parallel, a researcher determined 3D %TBSA using the BurnCase 3D program (RISC Software GmbH, Hagenberg, Austria). Demographic data and injury characteristics were also collected. Wilcoxon Signed Rank test was used to determine differences between each measure of %TBSA, with assessment of the influence of body mass index (BMI) and gender on accuracy. Results: Thirty-five patients were included in the study (6 female and 29 male). Average age was 47.5 years, with a median BMI of 26.6 kg/m 2 . %TBSA determined by BurnCase 3D program was statistically significantly different from conventional %TBSA assessment (p = 0.007), with the %TBSA measured using Burn Case 3D being lower than the %TBSA determined using conventional means (Lund and Browder Diagram) by 1.3% (inter-quartile range −0.6% to 5.6%). BMI and gender did not have an impact on the estimation of the %TBSA. Conclusion: The BurnCase 3D program underestimated %TBSA by 1.3%, as compared to conventional methods. Although statistically significant, this difference is not clinically significant as it has minimal impact on fluid resuscitation and on the decision to transfer a patient to a burn unit. 3D %TBSA evaluation systems are valid tools to estimate %TBSA, and should therefore be considered to improve %TBSA estimation at centers with no available experienced burn staff surgeon. Their use may ultimately prevent inappropriate transfers and allow for improved management of patients with acute burns.